2015
DOI: 10.1111/bph.13061
|View full text |Cite
|
Sign up to set email alerts
|

MPTP‐induced changes in hippocampal synaptic plasticity and memory are prevented by memantine through the BDNFTrkB pathway

Abstract: BACKGROUND AND PURPOSEMild cognitive deficit in early Parkinson's disease (PD) has been widely studied. Here we have examined the effects of memantine in preventing memory deficit in experimental PD models and elucidated some of the underlying mechanisms. EXPERIMENTAL APPROACHESI.p. injection of 1-methyl-4-phenyl-1,2,3,6-tetrahydro pyridine (MPTP) in C57BL/6 mice was used to produce models of PD. We used behavioural tasks to test memory. In vitro, we used slices of hippocampus, with electrophysiological, Weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 62 publications
8
57
1
Order By: Relevance
“…Neurotrophic factors are important regulators, which not only modulate synaptic transmission or neuronal cell death [27,28]. In this study, we found that after diabetic modeling, both of NGF and BDNF were down-regulated, while SFN treatment reversed the down-regulation.…”
Section: Discussionmentioning
confidence: 58%
“…Neurotrophic factors are important regulators, which not only modulate synaptic transmission or neuronal cell death [27,28]. In this study, we found that after diabetic modeling, both of NGF and BDNF were down-regulated, while SFN treatment reversed the down-regulation.…”
Section: Discussionmentioning
confidence: 58%
“…Although studies about synaptic transmission in hippocampus following MPTP lesion did not find significant differences of LTP from longer time of 30 min. post HFS or TBS22454647, further studies are needed to check whether our results are only related to the short phase of LTP.…”
Section: Discussionmentioning
confidence: 92%
“…However, Kim et al [92] demonstrated dopaminergic axon regrowth when the Bdnf gene was transduced 6 weeks after the axonal lesion. Moreover, BDNF treatment of brain slices from 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-treated mice was able to restore the impaired synaptic plasticity [102]. In addition, Hernandez-Chan et al [95] observed an increase in the striatal level of DA, while in SN there was no recovery of DA content.…”
Section: Study In Pd Animal Modelsmentioning
confidence: 99%